2002
DOI: 10.1016/s0014-5793(02)03725-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of GcpE, an essential enzyme of the non‐mevalonate pathway of isoprenoid biosynthesis

Abstract: The gcpE gene product controls one of the terminal steps of isoprenoid biosynthesis via the mevalonate independent 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway. This pathway is utilized by a variety of eubacteria, the plastids of algae and higher plants, and the plastid-like organelle of malaria parasites. Recombinant GcpE protein from the hyperthermophilic bacterium Thermus thermophilus was produced in Escherichia coli and puri¢ed under dioxygen-free conditions. The protein was enzymatically active in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 20 publications
2
103
1
3
Order By: Relevance
“…Based on the similarity of the EPR signals in GcpE and FTR we propose that the transient signal detected in GcpE is due to binding and stabilization of a radical-type intermediate by the 4Fe cluster. This is an important finding since several mechanisms have been proposed in the literature [10,13,16,33], but in only two papers was a direct role proposed for the 4Fe cluster [11,34].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the similarity of the EPR signals in GcpE and FTR we propose that the transient signal detected in GcpE is due to binding and stabilization of a radical-type intermediate by the 4Fe cluster. This is an important finding since several mechanisms have been proposed in the literature [10,13,16,33], but in only two papers was a direct role proposed for the 4Fe cluster [11,34].…”
Section: Resultsmentioning
confidence: 91%
“…The gcpE gene of T. thermophilus was overexpressed in an E. coli host and the gcpE product was purified as described previously [10]. This method generally yielded 25 mg of GcpE in 10 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Next, CDP-ME2P is converted to 2C-methyl-D-erythritol-2,4-cyclodiphosphate and CMP (18,19). The cyclodiphosphate then, in two enzyme-catalyzed stages, undergoes reduction and elimination to 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate and onto IPP and DMAPP (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Recent data has shown that (E)-4-hydroxy-3-methylbut-2-enyl diphosphate synthase (GcpE) and LytB proteins are iron-sulfur proteins containing a [4Fe-4S] 2ϩ cluster after reconstitution of the purified protein (12)(13)(14). GcpE catalyzes the reduction of MEcPP into HMBPP via two successive one-electron transfers (11,13). The last step of the MEP pathway is catalyzed by IspH (or LytB), which converts HMBPP into isopentenyl diphosphate or dimethylallyl diphosphate via two successive one-electron transfers (15).…”
mentioning
confidence: 99%